An improved, rapid competitive ELISA using a novel conserved 3B epitope for the detection of serum antibodies to foot-and-mouth disease virus. (September 2018) - Chung, Chungwon J.; Clavijo, Alfonso; Bounpheng, Mangkey A.; Uddowla, Sabena; Sayed, Abu; Dancho, Brooke; Olesen, Ian C.; Pacheco, Juan; Kamicker, Barbara J.; Brake, David A.; Bandaranayaka-Mudiyanselage, Carey L.; Lee, Stephen S.; et al.
The highly contagious foot-and-mouth disease virus (FMDV) afflicts cloven-hoofed animals, resulting in significant costs because of loss of trade and recovery from disease. We developed a sensitive, specific, and rapid competitive ELISA (cELISA) to detect serum antibodies to FMDV. The cELISA utilized a monoclonal blocking antibody specific for a highly conserved FMDV nonstructural 3B epitope, a recombinant mutant FMDV 3ABC coating protein, and optimized format variables including serum incubation for 90 min at 20–25°C. Samples from 16 animals experimentally infected with one FMDV serotype (A, O, Asia, or SAT-1) demonstrated early detection capacity beginning 7 d post-inoculation. All samples from 55 vesicular stomatitis virus antibody-positive cattle and 44 samples from cloven-hoofed animals affected by non-FMD vesicular diseases were negative in the cELISA, demonstrating 100% analytical specificity. The diagnostic sensitivity was 100% against sera from 128 cattle infected with isolates of all FMDV serotypes, emphasizing serotype-agnostic results. Diagnostic specificities of U.S. cattle ( n = 1135) and swine ( n = 207) sera were 99.4% and 100%, respectively. High repeatability and reproducibility were demonstrated with 3.1% coefficient of variation in percent inhibition data and 100% agreement using 2 kit lots and 400 negative control serum samples, with no difference between bench and biosafety cabinet operation. Negative results from vaccinated, uninfected cattle, pig, and sheep sera confirmed the DIVA (differentiate infected from vaccinated animals) capability. This rapid (<3 h), select agent–free assay with high sensitivity and specificity, DIVA capability, and room temperature processing capability will serve as a useful tool in FMDV surveillance, emergency preparedness, response, and outbreak recovery programs.